Implementation of Knowledge Management In Higher Education - Natalia Tri Astuti; Zetty Karyati; Martinus Tukiran (UJoST- Universal Journal of Science and Technology, 2023)
This study aims to determine the technical policies of supporting knowledge management in universities, apply knowledge management (KM), share knowledge in Knowledge Management (KM) and formulate hypotheses for the implementation of Knowledge Management. This research focuses on analyzing the application of Knowledge Management (KM) in universities which consists of the implementation of technical policies on knowledge management, the process of implementing management, and sharing knowledge in its implementation in universities. The importance of implementing knowledge management in universities is due to the high competitiveness of the organization. The success of an organization's survival and competitive ability is largely determined by Human Resources as an asset of the organization. The research method used is descriptive analysis with case studies. The method of data collection is carried out by interviews, observations, and documentation. Data analysis is carried out by reducing and displaying data, inferences and verification. The research results obtained are technical policies to support knowledge management in the Informatics study program. The application of knowledge management in Informatics Engineering can be seen from the development of HR competencies, the knowledge management process in line with the increasing focus on the implementation of teaching, research and community service with the use of information technology to support the management of knowledge available in libraries. Knowledge sharing in the study program environment is carried out through experiences and daily social interactions or known as individual tacit. Making individual tacit knowledge can be done with the presence of various meetings such as seminars, workshops, training and the like.